Germination and vigor of Capparis flexuosa L. seeds submitted to salt stress - Pacheco, Mauro V.; Ferrari, Cibele dos S.; Bruno, Riselane de L. A.; Araújo, Fernando dos S.; Silva, Givanildo Z. da; Arruda, Aubeny de A. (Brazilian Journal of Agricultural Sciences, 2022)
Capparis flexuosa L. is a forest species found in the Caatinga biome, which can be used to recover salinized soils. The aim of this study was to evaluate the germination and vigor of Capparis flexuosa seeds submitted to salt stress. The experimental design was completely randomized with treatments corresponding to the increasing levels of NaCl (0, 25, 50, 100, 200 and 400 mM) and four replications of 25 seeds each. The following parameters were evaluated: germination; first germination count; germination speed index (GSI); and length of the root and hypocotyl of the seedlings. The 200 mM concentration of salt provided good results for the germination percentage (79%) and did not influence seeds vigor evaluated by the seedlings performance on the first germination count (72%), GSI (3,87), root (1,28 cm) and hypocotyl length (1,8 cm). The seeds present the characteristic germination performance of halophyte plants, once they are highly tolerant to sodium chloride.